Meat Quality and Storage Stability of Turkeys Fed Diets Containing Synthetic and Non-Synthetic Additives - Kyakma, Samson Sukumun; Eko, S. J.; Tough, I. A.; Attah, S. (Journal of Science Research and Reviews, 2026)
Feed additives are groups of non-nutritive products added to rations to improve the efficiency of animal production and have shown antimicrobial, antifungal, antiviral, antioxidant, and sedative properties. The study investigated the performance, meat quality, and storage stability of turkeys fed diets containing different additives. A total of 150 day-old turkeys were purchased and brooded. After two weeks of brooding, the birds were balanced for weight and assigned to five (5) treatments, with each treatment containing 30 turkeys, with 10 turkeys in replicates of 3. Five diets consisting of basal diet with no additives (control), basal diet + 4 g/kg of cloves, basal diet + 4 g/kg of duam palm, basal diet + 2.0 mg/kg of vitamin C, and basal diet + 0.25 mg/kg of butylated hydroxytoluene (BHT) were used. The feeding trial lasted a period of 12 weeks. Data collected showed that the pH values recorded across dietary treatments ranged from approximately 6.5 to 7.0, with birds fed diets containing BHT and vitamin C showing slightly higher pH values compared to those fed cloves, duam palm, and the control diet. Potassium differed significantly (P<0.05). Cloves had the highest potassium, followed by intermediate values in BHT and Vitamin C, while control and duam palm were lower. The result of the microbial load demonstrated that aerobic plate count (APC), total coliform count (TCC), and total fungal count (TFC) increased progressively with storage duration. The results of this study demonstrate that dietary additives influence sensory quality of turkey meat in different ways. Vitamin C was most effective in enhancing flavour, while cloves maintained acceptable aroma and tenderness.